Identification of Polyvalent Vaccine Candidates From Extracellular Secretory Proteins in Vibrio alginolyticus - Peng, Yu-ming; Tao, Jian-jun; Kuang, Su-fang; Jiang, Ming; Peng, Xuan-xian; Li, Hui (Frontiers in Immunology, 2021)
Bacterial infections cause huge losses in aquaculture and a wide range of health issues in humans. A vaccine is the most economical, efficient, and environment-friendly agent for protecting hosts against bacterial infections. This study aimed to identify broad, cross-protective antigens from the extracellular secretory proteome of the marine bacterium Vibrio alginolyticus. Of the 69 predicted extracellular secretory proteins in its genome, 16 were randomly selected for gene cloning to construct DNA vaccines, which were used to immunize zebrafish (Danio rerio). The innate immune response genes were also investigated. Among the 16 DNA vaccines, 3 (AT730_21605, AT730_22220, and AT730_22910) were protective against V. alginolyticus infection with 47–66.7% increased survival compared to the control, while other vaccines had lower or no protective effects. Furthermore, AT730_22220, AT730_22910, and AT730_21605 also exhibited cross-immune protective effects against Pseudomonas fluorescens and/or Aeromonas hydrophila infection. Mechanisms for cross-protective ability was explored based conserved epitopes, innate immune responses, and antibody neutralizing ability. These results indicate that AT730_21605, AT730_22220, and AT730_22910 are potential polyvalent vaccine candidates against bacterial infections. Additionally, our results suggest that the extracellular secretory proteome is an antigen pool that can be used for the identification of cross-protective immunogens.